Effects of multiple doses of simvastatin and artesunate monotherapy on SCHISTOSOMA MANSONI adult worms during infection in hyperlidemic mice - Alencar, Alba Cristina Miranda de Barros; Silva dos Santos, Thais; Brandao-Bezerra, Luciana; Jose Lopes-Torres, Eduardo; Firmino Nogueira Neto , Jose; Heisler Neves, Renata; Roberto Machado Silva, Jose (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
A single dose of simvastatin and of artesunate monotherapy cause damage to the reproductive system of schistosomes as well as severe tegumental damage in male worms recovered from mice fed high-fat chow. This study aims to investigate whether treatment with multipledose regimes may offer more antischistosomal activity advantages than single daily dosing in mice fed high-fat chow. For this purpose, nine weeks post-infection, Swiss Webster mice were gavaged with simvastatin (200 mg/kg) or artesunate (300 mg/kg) for five consecutive days and euthanized two weeks post-treatment. Adult worms were analyzed using brightfield microscopy, confocal microscopy and scanning electron microscopy, presenting damages caused by simvastatin and artesunate to the reproductive system of males and females as well as tegument alterations, including peeling, sloughing areas, loss of tubercles, tegumental bubbles and tegument rupture exposing subtegumental tissue. The overall findings in this study revealed the potential antischistosomal activity of simvastatin and artesunate against Schistosoma mansoni adult worms, in addition to showing that multiple doses of either monotherapy caused severe damage to the tegument. KEY WORDS: Schistosoma mansoni; hyperlipidemia; simvastatin; artesunate; microscopy.